(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article discusses the methods and approaches used to develop self-assessment skills in schoolchildren through the use of reflective methods. During the analysis of lesson models, it was found that work aimed at developing self-assessment skills and reflective methods increases students' motivation to learn and contributes to the development of their ability to critically evaluate their actions. When writing the article, the ideas of J. Aimautov, based on self-awareness and conscious actions of the individual, were taken into account, and scientific works of Russian and American scientists were also used as a guide.